Global survey on durability variation – on the effect of the reference species - Stirling, R.; Alfredsen, Gry; Brischke, Christian; Wong, Andrew H.H (IRGWP, 2016)
Climate change due to anthropogenic emissions is the largest environmental challenge of our time. Forest-based value chains play an important role in reducing the accumulation of CO2 in the atmosphere. Maximizing the use of wood to tackle climate change requires improved understanding of the service life of timber products. This information can best be obtained from field testing and while there is an abundance of field performance data from sites all over the world, most of the data are not available in a form that can be utilised for service life models. The IRG Durability Database aims to improve the usability of existing performance data and create added value for durability research and service life prediction. The present paper takes the first steps in comparing global field test performance data from the IRG Durability Database for non-durable reference species. Data were obtained from six species above ground and ground contact field tests from 36 sites around the world. For each dataset, decay rates and service life (where applicable) were calculated. Datasets were then grouped together based on test method and species. Decay rate was faster and more uniform in ground contact than above ground. In ground contact, beech decayed most rapidly, followed by Norway spruce and Scots pine sapwood. All appeared to be suitable for use as reference species, however slow-grown spruce should be avoided. There were no statistically significant correlations between ground contact decay rate and the Scheffer Climate Index (SCI). In above ground tests, differences in decay rate were largely related to differences in moisture dynamics. Species with the greatest absorption and retention of water decayed most rapidly. Test methods that absorbed and retained the most moisture (e.g. painted L-joints) resulted in more rapid decay. Above ground decay rate and SCI were significantly correlated in two data sets that had a wide range of SCI values. Correlations were not significant when only European test sites were included. Estimating decay rate from field testing results in highly variable data. Comparing data from global test sites is made more difficult by the absence of common field testing standards.